Differential regulation of mGlu5R and ΜOPr by priming‐ and cue‐induced reinstatement of cocaine‐seeking behaviour in mice. (17th December 2014) - Georgiou, Polymnia; Zanos, Panos; Ehteramyan, Mazdak; Hourani, Susanna; Kitchen, Ian; Maldonado, Rafael; Bailey, Alexis
Abstract The key problem for the treatment of drug addiction is relapse to drug use after abstinence that can be triggered by drug‐associated cues, re‐exposure to the drug itself and stress. Understanding the neurobiological mechanisms underlying relapse is essential in order to develop effective pharmacotherapies for its prevention. Given the evidence implicating the metabotropic glutamate receptor 5 (mGlu5R), μ‐opioid receptor (MOPr), κ‐opioid receptor (ΚOPr) and oxytocin receptor (OTR) systems in cocaine addiction and relapse, our aim was to assess the modulation of these receptors using a mouse model of cue‐ and priming‐induced reinstatement of cocaine seeking. Male mice were trained to self‐administer cocaine (1 mg/kg/infusion, i.v.) and were randomized into different groups: (1) cocaine self‐administration; (2) cocaine extinction; (3) cocaine‐primed (10 mg/kg i.p.); or (4) cue‐induced reinstatement of cocaine seeking. Mice undergoing the same protocols but receiving saline instead of cocaine were used as controls. Quantitative autoradiography of mGlu5R, MOPr, KOPr and OTR showed a persistent cocaine‐induced upregulation of the mGlu5R and OTR in the lateral septum and central amygdala, respectively. Moreover, a downregulation of mGlu5R and MOPr was observed in the basolateral amygdala and striatum, respectively. Further, we showed that priming‐ but not cue‐induced reinstatement upregulates mGlu5R and MOPr binding in the nucleus accumbens core and basolateral amygdala, respectively, while cue‐ but not priming‐induced reinstatement downregulates MOPr binding in caudate putamen and nucleus accumbens core. This is the first study to provide direct evidence of reinstatement‐induced receptor alterations that are likely to contribute to the neurobiological mechanisms underpinning relapse to cocaine seeking.